MODULATORY ROLE OF ADRENALINE ON THE SECRETION OF CORTISOL FROM THE INTERRENAL CELLS IN CLARIAS BATRACHUS (LINNAEUS, 1758) - NEHAR, SHAMSHUN; RAZA, BUSHRA (Journal of the Inland Fisheries Society of India, 2021)
The functional interrelationship between chromaffin and interrenal cells in adrenal tissue is well established in higher vertebrates (Lesouhaitier et al., 1995; Mazzocchi et al., 1998). However, the interplay between interrenal and cromaffin cells is not very clear among teleosts. The adrenal tissue of bony fishes provide an excellent model to study such problems as both interrenal and chromaffin cells are intermingled closely around the cardinal vein in head kidney. The aim of this experiment was to study the effect of adrenaline, a major catecholamine of chromaffin origin, on the interrenal cortisol.